Allama Shibli and the early Muslim League: A dissenting voice - Islam, Arshad (IIUM Press, 2013)
The All-India Muslim League (AIML) was formed in 1906, with the primary aim to improve the educational and socioeconomic status of Muslims. Allama Shibli Nu‘mani (1857-1914) put forward an argument in support of Muslims recovering from the political stupor into which they had fallen after the British suppression of the 1857 uprising. He encouraged Muslims to participate in democratic politics in India, departing from the educational focus of his mentor, Sir Saiyid Ahmad Khan (1817-1898). Shibli advanced a strong critique of the Muslim League’s limited ambitions in comparison with the Indian National Congress (INC). His critique, notably in ironic and emotive poetry, significantly contributed to the national discussion pertaining to the Muslim League’s reform and restructure. Based on Shibli’s original writings, this paper analyses his critique of the Muslim League and his efforts to overhaul its structure and policies. It examines the response of the Muslim League to these critiques and studies the extent to which its structure and policies changed.